(untitled) (Indian Journal of Public Health Research & Development, 2020)
Introduction: Stimulation has a large effect on children’s development, but the impact of stimulation especially in infant’s communication development was unknown. The primary objective of the study was to evaluate the effect of stimulation on infant’s communication development at 2, 4 and 6 months of age. Method: This is a longitudinal study held in Kuantan Singingi District, Riau Province-Indonesia from January to October 2017. We enrolled all newborns whose parents lived and settled in Kuantan Singingi district and had normal delivery. Newborn with major congenital abnormalities, pathological jaundice, low birth weight and whose mother were smoking were excluded. Data of infant’s communication development and parent’s stimulation were collected at 2, 4 and 6 months. the Age and Stages Questionnaire third edition (ASQ-3) was administered to assess infant’s communication development and the Infant/toddler Home Observation for Measurement of the Environment (HOME) Inventory was administered to assess parent’s stimulation. We analyzed the relationship between parent’s stimulation and infant’s communication development at 2, 4 and 6 months using logistic regression analysis. Results: We enrolled 474 newborns and their parents. Compared to less stimulated infants, infants who got enough stimulation by their parents had better communication developments at 2 months (OR 11.1 95% CI: 3.8-32.4), 4 months (OR 2.6 95% CI: 1.3-5.3) and 6 months (OR: 2.2 95% CI 1.1-4.3). Conclusion: Giving enough stimulation by parents can affect the communication developments of their infants.